Project Flyer - RiskBenefit4EU (Partnering to strengthen the Risk Benefit Assessment within EU using a holistic approach) - Alvito, Paula (2018)
Human diet leads to public health benefits and potential risks. The balance between risks and benefits is of interest to food authorities developing food policy and consumer advice, to businesses developing new food products, and to consumers considering dietary changes. The new approach of Risk-benefit assessment (RBA) intends to estimate the overall impact of food consumed on human health by assessing benefits and risks associated with exposure (or lack of exposure) to a particular food or food component or diet and by integrating all into a comparable measure. Within the EU, the RBA methodologies are far from being developed, representing a research gap needing attention from academics, researchers and policy makers. The aim of this project is to strengthen the EU capacity to perform RBA in foods, considering risks and benefits in the areas of microbiology, nutrition and chemistry, through the development of a harmonized framework that will be available to EU member states organizations.